Values and their relationship with emotion processing and physical and psychological symptoms among Jewish and Arab breast cancer survivors - Hebi, Maimounah; Czamanski-Cohen, Johanna; Azaiza, Faisal; Weihs, Karen L. (Frontiers in Psychology, 2024)
Individuals from different cultures differ in their values, which may affect emotion processing (EP) and physical and psychological symptoms in breast cancer (BC) survivors. This crosssectional study investigated how EP including acceptance, expression, and awareness, as well as avoidance and approach coping, may mediate the relationship between conservation values and symptoms of pain, fatigue, and depression among women Arab (n = 62) and Jewish (n = 179) BC survivors in Israel. Conservation values include tradition, conformity, and security. Depression and fatigue were negatively correlated with acceptance of emotions, while showing a positive correlation with avoidance and conservation levels. Emotion processing totally mediated the relationships between conservation and both fatigue and depression. Arab women reported higher levels of different values, emotional acceptance, pain, fatigue, and depression symptom CULTURE & EMOTION PROCESSING: BREAST CANCER 2 compared to Jewish women. Conservation is higher in Arab women and correlated with approach coping which was not the case in Jewish women. Additionally, the relationship of avoidance coping was positive in Arab women, was not significant in Jewish women. Avoidance coping had a positive relationship with fatigue in the Jewish, but not the Arab women. Similarly, approach coping was negatively related to depression in Jewish women, but not in Arab women. Thus, we found cultural differences are important for understanding the experience of cancer in individuals from different cultures. Future interventions for more conservative BC survivors should take culture into account.